Conservative treatment of older adult patients with shoulder diseases: a narrative review - Kook Jong Kim; Ho-Seung Jeong (The Ewha Medical Journal)
The purpose of this review is to provide a comprehensive guide for managing older adult patients with shoulder diseases, specifically rotator cuff tears and osteoarthritis, and to explore effective nonsurgical treatment options. Chronic rotator cuff tears are typically degenerative, whereas acute tears result from trauma. A key feature of these tears is tendon degeneration accompanied by type III collagen predominance, predisposing tears to progression. Osteoarthritis in the glenohumeral joint arises from wear-and-tear changes that compromise cartilage integrity, leading to pain and restricted motion. Accurate clinical assessment and imaging, including plain radiographs, ultrasonography, and MRI, facilitate diagnosis and guide treatment. The physic-al examination emphasizes range of motion, rotator cuff strength, and scapular stability. Management strategies prioritize pain relief, function preservation, and improving mobility. Nonsurgical modalities, including exercise, manual therapy, and activity modification, constitute first-line treatments, especially for older adults. Pharmacological approaches involve NSAIDs, corticosteroid injections, and neuropathic pain medications. Steroid injections have short-term benefits, but repeated treatments may compromise tissue integrity. Platelet-rich plasma is a regenerative option that may improve tendon healing, but mixed findings highlight the need for further investigation. A structured physical therapy program focusing on range of motion and strengthening is essential, with alternative interventions used judiciously. Patients should be counseled regarding the potential progression of tears and the possible need for future surgical intervention if nonsurgical methods are unsuccessful. Multimodal approaches, including joint mobilization and personalized exercise regimens, hold potential for optimizing functional outcomes and supporting independence in older adults.